In vitro evaluation of Candida albicans and Candida parapsilosis adhesion in protocol-type prosthesis bases - Portella, Fernando Freitas; Spielmann, César; Gälzer, Andressa; Flavia-Gazzoni, Alexandra; Rivaldo, Elken Gomes (Revista InterScientia, 2024)
The genus Candida has been mentioned as one of the main causes of infections in the oral cavity. In addition to Candida albicans, another species that has been identified on oral surfaces and dental prostheses is Candida parapsilosis. The aim of the present study was to evaluate the adhering of Candida albicans and Candida parapsilosis on different materials used in protocol type prosthesis bases. Samples were divided into three groups made by the CAD/CAM technique from cobalt-chromium, titanium and zirconium blocks added to an acrylic resin control group. The yeasts were seeded in a fungal suspension at an inoculum concentration of 106 cells/ml and incubated at 37°C for 48 hours. After counting, the colony forming units per ml were photographed. In addition, the samples were analyzed under a scanning electron microscope. Descriptive analysis was performed for the samples in each group and a comparison test was performed using the analysis of variance with Tukey's multiple comparisons, considering p<0.05 as significant. Candida albicans adhered significantly less on titanium than on the other three materials. Candida ssp had a different colonization behavior in the four materials and a significant difference between the species was found in the titanium, acrylic and zirconium (p<0.05). It can be concluded that titanium presented the lowest adhesion. DOI https://zenodo.org/records/10684904